Synthesis, Characterizations, and Electrochemical Performances of Highly Porous, Anhydrous Co0.5Ni0.5C2O4for Pseudocapacitive Energy Storage Applications - Mishra N.K.; Mondal R.; Maiyalagan T.; Singh P. (My University, 2025)
Electrochemical energy storage relies essentially on the development of innovative electrode materials with enhanced kinetics of ion transport. Pseudocapacitors are excellent candidates to bridge the performance gap between supercapacitors and batteries. Highly porous, anhydrous Ni0.5Co0.5C2O4 is envisaged here as a potential electrode for pseudocapacitor applications, mainly because of its open pore framework structure, which poses inherent structural stability due to the presence of planar oxalate anions (C2O42-), and active participation of Ni2+/3+ and Co2+/3+ results in high intercalative charge storage capacity in the aqueous KOH electrolyte. The Ni0.5Co0.5C2O4 electrode shows specific capacitance equivalent to 2396 F/g at 1 A/g in the potential window of 0.6 V in the aqueous 2 M KOH electrolyte by galvanostatic charge/discharge experiments. Predominant pseudocapacitive mechanism seems to operative behind high charge storage due to active participation of Ni2+/3+ and Co2+/3+ redox couple as intercalative (inner) and surface (outer) charges stored by porous anhydrous Co0.5Ni0.5C2O4 were close to high 38 and 62% respectively. Further, in full cell asymmetric supercapacitors (ASCs) in which porous anhydrous Co0.5Ni0.5C2O4 was used as the positive electrode and activated carbon (AC) was utilized as the negative electrode, in the operating potential window 1.6 V, the highest specific energy of 283 W h/kg and specific power of ∼817 W/kg were achieved at 1 A/g current rates. Even at a very high power density of 7981 W/kg, the hybrid supercapacitor still attains an energy density of ∼75 W h/kg with high cyclic stability at a 10 A/g current rate. The detailed electrochemical studies confirm higher cyclic stability and a superior electrochemical energy storage property of porous anhydrous Co0.5Ni0.5C2O4, making it a potential pseudocapacitive electrode for large energy storage applications. © 2022 The Authors. Published by American Chemical Society.